08/13/2011, 04:02 PM

a(b(x)) = solve(b(x)*x)

b(c(x)) = solve(c(x)*x)

c(a(x)) = solve(a(x)*x)

it seems closely related to iterations , recursions and continued fractions but its still somewhat puzzling ...

there are many equivalent equations , but i dont know if they are helpfull.

perhaps taking derivates on both sides will help ?

regards

tommy1729

b(c(x)) = solve(c(x)*x)

c(a(x)) = solve(a(x)*x)

it seems closely related to iterations , recursions and continued fractions but its still somewhat puzzling ...

there are many equivalent equations , but i dont know if they are helpfull.

perhaps taking derivates on both sides will help ?

regards

tommy1729